2020
DOI: 10.1051/m2an/2019070
|View full text |Cite
|
Sign up to set email alerts
|

A minimum entropy principle in the compressible multicomponent Euler equations

Abstract: In this work, the space of admissible entropy functions for the compressible multicomponent Euler equations is explored, following up on [Harten, J. Comput. Phys., 49 (1), 1983, pp. 151-164]. This effort allows us to prove a minimum entropy principle on entropy solutions, whether smooth or discrete, in the same way it was originally demonstrated for the compressible Euler equations by [Tadmor, Appl. Numer. Math., 49 (3-5), 1986, pp. 211-219].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…As observed in [31], the function H 0 (S), although not smooth, can be written as the limit of a sequence of smooth functions satisfying (14); see also [6,Section 3.1] for a detailed review. Therefore, by passing to the limit, the inequality (26) holds for H = H 0 , which gives…”
Section: Minimum Principle Of the Specific Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in [31], the function H 0 (S), although not smooth, can be written as the limit of a sequence of smooth functions satisfying (14); see also [6,Section 3.1] for a detailed review. Therefore, by passing to the limit, the inequality (26) holds for H = H 0 , which gives…”
Section: Minimum Principle Of the Specific Entropymentioning
confidence: 99%
“…Jiang and Liu proposed new IRP limiters for the DG schemes to the isentropic Euler equations [20], the compressible Euler equations [17], and general multi-dimensional hyperbolic conservation laws [18]. Gouasmi et al [6] proved a minimum entropy principle on entropy solutions to the compressible multicomponent Euler equations at the smooth and discrete levels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical experiments showed that the ES scheme we constructed is no exception. We stress that these anomalies, which are not present in the single component case, violate neither entropy stability nor a minimum principle of the specific entropy [64]. The remedies to the pressure oscillations problem typically consist in giving up on conservation of total energy [45,44,38,43], which can impair the ability of the scheme to properly capture shocks.…”
Section: Discussionmentioning
confidence: 96%
“…Proof Twice differentiability is straightforward from (2.16). To prove the convexity we use the trick introduced in [28] and also used in [24] to prove that the Hessian of the entropy H η is congruent to the following strictly convex diagonal matrix:…”
Section: Entropy Pairmentioning
confidence: 99%